Boiler Ash of Oil Palm Shell as Adsorbent for Lead Adsorption - Nurdiansyah, Nurdiansyah; Hidayat, Chusnul; Suroto, Dian Anggraini (agriTECH, 2025)
Palm oil shells and fibers are widely used as fuel for factory boiler furnaces. However, boiler ash residue produced is often underutilized. This study aims to explore the use of boiler bottom ash (BBA) as an adsorbent for the adsorption of lead (Pb) and its subsequent application in palm oil mill effluent (POME) purification for water dilution in crude palm oil (CPO) processing. BBA was activated using 0.2, 0.4, 0.6, and 0.8 mol/L potassium hydroxide (KOH) solutions for 24 hours, and the carbonation was conducted at 400°C for 60 minutes. Factors, such as the concentration of KOH for BBA activation, pH levels, adsorption temperature, adsorption kinetics, and the application of the adsorbent in POME purification for water dilution in the CPO processing model, were evaluated. The results showed that the optimal KOH concentration was 0.4 mol/L, as determined by SEM, EDX, and lead adsorption analysis. The maximum adsorbent capacity of approximately 0.43 mg/g was obtained at 50°C and pH 4.6, with an adsorption rate constant of 5.97 per minute. The results also showed that the adsorption process followed the Langmuir model. In addition, the adsorption activation energy and the Arrhenius constant values were -28675.82 J/mol and 0.0001, respectively. The use of POME filtrate for water dilution had no effect on the free fatty acids, water content, impurities, or DOBI (Deterioration Bleachability of Index) in CPO. Lead value showed significant differences in all treatments without dilution. These results indicate that BBA activated with KOH can function as an adsorbent to reduce lead content. POME purified with BBA adsorbent has the potential to be used as diluent water in CPO processing to reduce raw water use and ultimately decrease POME production.